Transforming Food Security for Economic Independence in Indonesia: Mentransformasi Ketahanan Pangan untuk Kemandirian Ekonomi di Indonesia - Sari, Endang Kumala; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2024)
Food security, crucial for ensuring access to sufficient, nutritious food, is a key government focus. This study examines the food security program in Watutulis Village, Prambon District, aimed at achieving economic independence. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation, with purposive sampling of knowledgeable informants. Results show successful efforts in food production and access, notably through fish farming, but limited utilization of these resources beyond household consumption. The study suggests enhancing collaborations with local businesses to create value-added food products, driving economic growth and independence for the village. Highlights: Successful food production and access via fish farming. Limited food utilization beyond household consumption. Need collaboration with local businesses for economic growth. Keywords: food security, Watutulis Village, economic independence, food utilization, qualitative research